Post-COVID-19 cognitive symptoms in patients assisted by a teleassistance service: a retrospective cohort study - Bonfim, Lívia Paula Freire; Correa, Thais Rotsen; Freire, Bruno Cabaleiro Cortizo; Pedroso, Thais Marques; Pereira, Daniella Nunes; Fernandes, Thalita Baptisteli; Kopittke, Luciane; Oliveira, Clara Rodrigues Alves de; Teixeira, Antonio Lucio; Marcolino, Milena Soriano (Frontiers in Public Health, 2024)
Introduction Four years after the onset of the COVID-19 pandemic, the frequency of long-term post-COVID-19 cognitive symptoms is a matter of concern given the impact it may have on the work and quality of life of affected people. Objective To evaluate the incidence of post-acute COVID-19 cognitive symptoms, as well as the associated risk factors. Methods Retrospective cohort, including outpatients with laboratory-confirmed COVID-19 and who were assisted by a public telehealth service provided by the Telehealth Network of Minas Gerais (TNMG), during the acute phase of the disease, between December/2020 and March/2022. Data were collected through a structured questionnaire, applied via phone calls, regarding the persistence of COVID-19 symptoms after 12 weeks of the disease. Cognitive symptoms were defined as any of the following: memory loss, problems concentrating, word finding difficulties, and difficulty thinking clearly. Results From 630 patients who responded to the questionnaire, 23.7% presented cognitive symptoms at 12 weeks after infection. These patients had a higher median age (33 [IQR 25–46] vs. 30 [IQR 24–42] years-old, p = 0.042) with a higher prevalence in the female sex (80.5% vs. 62.2%, p < 0.001) when compared to those who did not present cognitive symptoms, as well as a lower prevalence of smoking (8.7% vs. 16.2%, p = 0.024). Furthermore, patients with persistent cognitive symptoms were more likely to have been infected during the second wave of COVID-19 rather than the third (31.0% vs. 21.3%, p = 0.014). Patients who needed to seek in-person care during the acute phase of the disease were more likely to report post-acute cognitive symptoms (21.5% vs. 9.3%, p < 0,001). In multivariate logistic regression analysis, cognitive symptoms were associated with female sex (OR 2.24, CI 95% 1.41–3.57), fatigue (OR 2.33, CI 95% 1.19–4.56), depression (OR 5.37, CI 95% 2.19–13.15) and the need for seek in-person care during acute COVID-19 (OR 2.23, CI 95% 1.30–3.81). Conclusion In this retrospective cohort of patients with mostly mild COVID-19, cognitive symptoms were present in 23.7% of patients with COVID-19 at 12 weeks after infection. Female sex, fatigue, depression and the need to seek in-person care during acute COVID-19 were the risk factors independently associated with this condition.